Impact of Tourism Activities on the Economy of the Community in The Coastal Area of Langkawi Island, Malaysia - Shafikhullah, Siti Nor Azalia; Nayan, Nasir (Forum Ilmu Sosial, 2021)
This article aims to identify the impact of tourism development among the community in Langkawi Island, Malaysia. This study uses a quantitative approach. The data used impact data collected primarily using a questionnaire given to 400 respondents among household heads. The analysis used is descriptive. The results showed that there must be a development impact, with more than 64 percent agreeing on the existence of the impact and felt by them in various economic matters. More than 80 percent of the community noted increased living standards, employment opportunities, income, investment interest, business, and ancillary income. This increase also negatively impacted the increase in prices of goods, services, real estate, housing, and cost of living. Significant changes can sprout up with the ability to own luxury items such as computers, mobile phones, ovens, microwave ovens, washing machines, air conditioners, vacuums, and water filters compared to 2000. In conclusion, the development of tourist land use dominates Langkawi Island, particularly positively impacting the local economy. The implications of this study can show how specific development planning such as tourism can have a positive impact and needs to remain further enhanced with the presence of specialized agencies such as the Langkawi Development Authority (LADA).